Correlation between critical thinking and emotional intelligence: a national cross-sectional study on operating room nursing students in Iran - Fereidouni Armin; Teymoori Esmaeil; Bahmani Tayebeh; Sabet Hamid Reza; Maleki Zahra; Gharibi Mina (Frontiers of Nursing, 2024)
According to the World Federation of Medical Education, critical thinking should be part of the training of medical and paramedical students. Professionals can improve the quality of care of patients after surgery by having or acquiring this skill in health care. Also, Emotional intelligence is introduced as an important and effective factor on the professional performance and mental health of healthcare professionals. Thus, the present study was designed and implemented to determine the relationship between emotional intelligence and critical thinking among operating room nursing students of medical sciences universities in Iran.